A Real-World, Prospective, Multicenter, Single-Arm Observational Study of Duloxetine in Patients With Major Depressive Disorder or Generalized Anxiety Disorder - Szekeres, Gyorgy; Rozsa, Sandor; Dome, Peter; Barsony, Gabor; Gonda, Xenia (Frontiers in Psychiatry, 2021)
Background: Suboptimal treatment response during anti-depressive treatment is fairly common with the first antidepressant (AD) choice, followed by switching to another agent in the majority of cases. However, the efficacy of this strategy over continuation of the original agent is less solidly documented in real-life studies. The aim of our present study was to ascertain the effects of switching to duloxetine following inadequate response to prior ADs on general illness severity, pain, and health-related quality of life in a large sample of major depressive disorder (MDD) and generalized anxiety disorder (GAD) patients in a prospective, real-world, multicenter, observational study. Methods: A total of 578 participants with MDD or GAD were enrolled in 58 outpatient sites in an 8-week, single-arm, open-label, flexible-dose trial with duloxetine. Severity of symptoms [with Clinical Global Impression-Severity (CGI-S) and Clinical Global Impression-Improvement (CGI-I)], severity of pain (with a Visual Analog Scale), satisfaction with current treatment, and health-related quality of life [with the three-level version of the EuroQol five-dimensional questionnaire (EQ-5D-3L)] measures were recorded at baseline and at follow-up visits 4 and 8 weeks after initiation of treatment. Data were analyzed using ANOVA and mixed linear models. Results: 565 patients completed the study and comprised the analyzed dataset. Results indicated that severity of illness significantly decreased over the 8 weeks of the study and already at 4 weeks in both patient groups. Overall quality of life and all of its subindicators also significantly improved in both patient groups and so did subjective experience of pain. Satisfaction with current treatment also significantly increased during the study period. Frequency of side effects was low. In both GAD and MDD groups, two patients dropped out of the study due to adverse effects, leading to treatment termination in four cases (0.7%). Conclusions: This 8-week, multicenter, flexible-dosing, single-arm, open-label, observational real-life study in MDD and GAD patients switched to duloxetine after inadequate response or low tolerability to other ADs showed a significant positive effect on all outcome measures, including a significant decrease in illness severity as well as significant overall symptomatic improvement, with good tolerability.